2021
DOI: 10.1007/s10459-021-10048-9
|View full text |Cite
|
Sign up to set email alerts
|

Japanese medical learners’ achievement emotions: Accounting for culture in translating Western medical educational theories and instruments into an asian context

Abstract: Medical learners’ achievement emotions during educational activities have remained unexamined in Asian cultural contexts. The Medical Emotion Scale (MES) was previously developed to assess achievement emotions experienced by North American medical learners during learning activities. The goal of this study was to create and validate a Japanese version of the Medical Emotion Scale (J-MES). We translated the MES into Japanese and conducted two initial validation studies of the J-MES. In the first pilot study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“… 21 , 22 According to educational theories, arranging the learning environment is also important to maintain the well‐being of the trainees. 23 , 24 Several studies have demonstrated the relationship between the pediatric residents' learning environment and their frequency of burnout. 1 , 2 , 6 Specifically, the peer mentorship program has been suggested to provide the residents with “safe” training circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 22 According to educational theories, arranging the learning environment is also important to maintain the well‐being of the trainees. 23 , 24 Several studies have demonstrated the relationship between the pediatric residents' learning environment and their frequency of burnout. 1 , 2 , 6 Specifically, the peer mentorship program has been suggested to provide the residents with “safe” training circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, multi‐centered trials have focused on designing flexible shiftwork to improve residents' wellness and patients' safety 21,22 . According to educational theories, arranging the learning environment is also important to maintain the well‐being of the trainees 23,24 . Several studies have demonstrated the relationship between the pediatric residents' learning environment and their frequency of burnout 1,2,6 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the score for perceived test difficulty was similar to those in previous studies. While data on individual perceptions is less objective than quantitative data, the examinee's perceptions are essential for inferring the scoring phase in Kane's framework ( 15 ). Our inferences revealed that the experts and trainees evaluated the Jpem-SCT as having high clarity and usability, indicating that the TRAPD team translation model was effective.…”
Section: Discussionmentioning
confidence: 99%
“…Kane emphasized implication as the most important step in the validity argument in real-world settings. Based on the obtained data, we examined validity evidence for the Jpem-SCT in terms of Kane's validity arguments ( 14 ), as this framework is useful for validating translated assessment tools ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to educational theories, arranging the learning environment is also important to maintain the well-being of the trainees [16,17]. Several studies have demonstrated the relationship between the pediatric residents' learning environment and their frequency of burnout [1,3].…”
Section: Discussionmentioning
confidence: 99%